Low Temperature Synthesis of Superparamagnetic Iron Oxide (Fe3O4) Nanoparticles and Their ROS Mediated Inhibition of Biofilm Formed by Food-Associated Bacteria - Al-Shabib, Nasser A.; Husain, Fohad Mabood; Ahmed, Faheem; Khan, Rais Ahmad; Khan, Mohammad Shavez; Ansari, Firoz Ahmad; Alam, Mohammad Zubair; Ahmed, Mohammed Asif; Khan, Mohd Shahnawaz; Baig, Mohammad Hassan; Khan, Javed Masood; Shahzad, Syed Ali; et al. (Frontiers in Microbiology, 2018)
In the present study, a facile environmentally friendly approach was described to prepare monodisperse Fe3O4 nanoparticles by low temperature solution route. The synthesized nanocomposites were characterized using x-ray diffraction spectroscopy (XRD), Raman spectroscopy, field emission scanning electron microscopy (FESEM) measurements, FTIR, and TGA analyses. XRD patterns revealed the high crystalline quality of the nanoparticles. SEM micrographs showed the monodispersed Fe3O4 nanoparticles with size ranging from 6-9 nm. Synthesized superparamagnetic iron oxide (Fe3O4) nanoparticles demonstrated MICs of 32, 64 and 128 µg/ml against Gram negative bacteria i.e. S. marcescens, E. coli, and P. aeruginosa, respectively and 32 µg/ml against Gram positive bacteria L. monocytogenes. Iron oxide nanoparticles (IOPNs) demonstrated significant reduction of alginate and exopolysaccharide production and subsequently demonstrated broad-spectrum inhibition of biofilm ranging from 16-88% in the test bacteria. Biofilm reduction was also examined using SEM and CLSM. Interaction of IONPs with bacterial cells generated ROS and this ROS caused cell death leading to reduced biofilm formation. We for the first time report that these IONPs were effective in obliterating pre-formed biofilms. Thus, it is envisaged that these nanoparticles with broad-spectrum biofilm inhibitory property could be exploited in the food industry as well as in medical settings to curtail biofilm based infections and losses.